Water Absorption Kinetics of Pearl Millet Grains - Chauhan, S. S.; Jha, S. K.; Jha, G. K.; Sharma, D. K. (Journal of Agricultural Engineering, 2014)
Water absorption characteristics of pearl millet (PC 443) were evaluated in the temperature range of ambient (16°C) to 100°C. Water absorption by the grain increased with increase in temperature. The increase in water absorption by the grain was more rapid at temperatures 70°C and above. The initial rates of hydration at temperatures 16, 30, 40, 50, 60, 70, 80, 90 and 100°C were 14.2, 20.5, 24, 32.9, 43.2, 47.6, 94.7, 136.3, and 142.7 g.kg.dm-1.min-1, respectively. The rate of hydration decreased with increase in hydration time and approached very low value (≤0.1 g.water.kg.dm-1.min-1) corresponding to the grain moisture contents 16, 19, 22, 25, 33, 39, 46% (wb), respectively, at 16, 30, 40, 50, 60, 70, 80°C. The maximum moisture content after the hydration of pearl millet grain could be 48%, beyond which bursting of grains was observed. Moisture diffusivity varied from 2.13x10-4 m2.s-1 to 30.56x10-1 m2.s-1, with average value of 9.99x10-3 m2.s-1 during hydration. Activation energy for hydration of pearl millet was found to be 55.71 kJ.mol-1. Page model was found to be the best for modelling hydration characteristics of pearl millet.